2016
DOI: 10.1021/acs.jpcc.6b00745
|View full text |Cite
|
Sign up to set email alerts
|

An External Electric Field Manipulated Second-Order Nonlinear Optical Switch of an Electride Molecule: A Long-Range Electron Transfer Forms a Lone Excess Electron Pair and Quenches Singlet Diradical

Abstract: An electride molecule e–···K­(1)+···calix­[4]­pyrrole···K­(2)+···e– as an external electric field (F) manipulated nonlinear optical (NLO) switch is designed theoretically for the first time. As this molecule is an unusual singlet diradical electride molecule with two easily driven excess electrons (by electric field) at two opposite ends of the molecule, a novel switching mechanism of electronic structure isomerization emerges as a distinctive nonbonding evolution in the electride molecule. A small electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 106 publications
(171 reference statements)
2
60
0
Order By: Relevance
“…(EEF ¼ 30 Â 10 À4 (a.u. )), as well as Be 6 Li 8 and Be 6 Li 14 , were reported by Li and Hou et al 19,20,50 It is worth noticing that the above-mentioned NLO molecular switches are all electride molecules. 19,20,50 To the best of our knowledge, NLO switch molecules of an inorganic alkalineearth alkalide have not been reported yet.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…(EEF ¼ 30 Â 10 À4 (a.u. )), as well as Be 6 Li 8 and Be 6 Li 14 , were reported by Li and Hou et al 19,20,50 It is worth noticing that the above-mentioned NLO molecular switches are all electride molecules. 19,20,50 To the best of our knowledge, NLO switch molecules of an inorganic alkalineearth alkalide have not been reported yet.…”
Section: Introductionmentioning
confidence: 76%
“…Excess electron compounds have been proven to serve as potential candidates for NLO materials with excellent NLO responses. [15][16][17][18][19][20] In recent years, studies on excess electron compounds have gained plentiful attention. [21][22][23][24][25][26][27][28][29] Alkalides and electrides are typical representatives of excess electron compounds, where anion sites are occupied by anionic alkalis and trapped electrons, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Liu et al reported that AISC systems with Ca as an alkaline earth metal shows intermediate diradical character ( y ) of sσ‐orbital of Ca atom . As the second‐order NLO materials, the similar structures of AISCs, like the alkali metal inverse sandwich molecules and all‐metal electrode molecules with the structure, in which the alkaline earth metals sandwich metal clusters, exhibit large first hyperpolarizabilities (the molecular‐level origin of 2 nd ‐order NLO properties) and act as external‐field‐induced NLO switch. Krieck et al have synthesized AISCs with Ca as an alkaline earth metal , .…”
Section: Introductionmentioning
confidence: 99%